Research highlights from the Small Ruminant Collaborative Research Support Program: the dual-purpose goat (DPG) - Semenye, P.P.; Mbabu, A.N.; Mwandotto, B.; Nyaribo, F.B.; Onim, J.M.; Rurangirwa, F.R. (1992)
The Small Ruminant Collaborative Research Support Program (SR-CRSP) in Kenya is engaged in a multidisciplinary research programme with a farming-system perspective. Its overall objective is to carry out research on dual-purpose goat production systems, to enhance production of food protein through meat and milk, and to improve cash flow through sale of goats and products in small-scale intensive farming systems. Research highlights are presented on feed production, preservation and utilisation, goat production and management, development and performance testing of a composite dual-purpose goat breed, immunoprophylaxis and diagnosis of contagious caprine pleuropneumonia (CCPP), heartweater and helminthiasis. The economy of raising dual-purpose goats, their acceptability and the utilisation of their products by farmers in western Kenya are also highlighted.